Proactive psychological and psychiatric approach in optimizing the diagnostic algorithm for patients with chronic pain - Asanova, Азізе; Khaustova, Олена (Psychosomatic Medicine and General Practice, 2024)
Background. Chronic pain is one of the most common problems in modern medicine. War, stressful psychological and social factors, and physical inactivity contribute to the rapid growth of specific conditions for the onset and spread of pain. Accordingly, in the acute phase of the pathological process of inflammation or injury, biological factors released due to tissue damage play a leading role in pain mediation, but over time, the pathological process can resolve or continue and move into a chronic phase, which is certainly influenced by negative social and psychological factors. A proactive, personalized psychological and psychiatric approach to the diagnosis and treatment of chronic pain contributes to an earlier and more accurate determination of the etiopathogenetic nature of pain (primary, secondary, mixed; nociceptive, neuropathic, neuroplastic). In addition, it is important to note that the diagnosis of chronic pain is often complicated due to the mixed nature of pain, when several mechanisms of pain sensations are simultaneously present. Materials and methods. In order to optimize the diagnostic algorithm for patients with chronic pain and based on our own clinical experience with this category of patients, we conducted a content analysis of scientific sources in Ukrainian and English-language over the past 10 years. The search was made using Pubmed, CrossRef, Scopus databases. Results. Based on a review of current scientific research and our own two-year clinical experience in the management of patients with chronic pain, we proposed a diagnostic algorithm that includes a sequence of stages, somatic, mental and social verification, and is based on a psychological and psychiatric approach, takes into account the new ICD-11 diagnostic criteria and helps to establish a diagnosis in the paradigm of the biopsychosocial model of pain by identifying biological (physical), psychological (mental) and social factors that affect the etiology of pain disorder. Conclusions. Proposed optimized diagnostic algorithm is based on a psychological and psychiatric approach and makes it possible to take into account biological, psychological and social factors for the further effective management of patients with chronic pain. Key words: Chronic pain, pain diagnostics, innovative management technologies, diagnostic algorithms, psychological and psychiatric approach, biopsychosocial model of pain, artificial intelligence.